2021
DOI: 10.1039/d1cp01022k
|View full text |Cite
|
Sign up to set email alerts
|

C9N4 and C2N6S3 monolayers as promising anchoring materials for lithium–sulfur batteries: weakening the shuttle effect via optimizing lithium bonds

Abstract: The notorious polysulfide shuttle effect is a crucial factor responsible for the degradation of Li-S batteries. A good way to suppress the shuttle effect is to effectively anchor the dissoluble...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…In addition, C 2 N shows highly negative Gibbs free energy for Li n -C 2 N and strong adsorption capability for Li 2 S. Its high LiPSs adsorption capability was also confirmed by Zhang et al using firstprinciples calculations [114]. Comparing four nonmetallic layered materials (graphene, BN, C 2 N, and C 3 N 4 ), C 3 N 4 and C 2 N exhibit stronger LiPSs adsorption capability through the [116]. With increased electronic conductivity of C x N y , the LiPSs adsorbed can directly lose/gain electrons to be oxidized/ reduced, which avoids the loss of LiPSs and improve the rate capability of Li-S batteries.…”
Section: Other C X N Y Materialsmentioning
confidence: 61%
“…In addition, C 2 N shows highly negative Gibbs free energy for Li n -C 2 N and strong adsorption capability for Li 2 S. Its high LiPSs adsorption capability was also confirmed by Zhang et al using firstprinciples calculations [114]. Comparing four nonmetallic layered materials (graphene, BN, C 2 N, and C 3 N 4 ), C 3 N 4 and C 2 N exhibit stronger LiPSs adsorption capability through the [116]. With increased electronic conductivity of C x N y , the LiPSs adsorbed can directly lose/gain electrons to be oxidized/ reduced, which avoids the loss of LiPSs and improve the rate capability of Li-S batteries.…”
Section: Other C X N Y Materialsmentioning
confidence: 61%
“…Previous ab initio calculations have demonstrated that N, S-doped carbon materials can effectively chemically bound to the Li + and S n 2− of polysulfides based on the formation of Li–N bonds and S–S interactions. 36–39…”
Section: Resultsmentioning
confidence: 99%
“…S2, ESI †), 46,47 To gain a deeper insight into the interaction between cathode hosts and Se 8 /Na 2 Se n , the charge density difference of Se 8 /Na 2 Se n on M 2 CO 2 /Zn-M 2 CO 2 was performed to investigate charge transfer during the adsorption process. 49 In the case of Se 8 molecule adsorption on the surface, only a small amount of electron transfer occurs, demonstrating that the interaction between Se 8 and the substrate is mainly governed by vdWs physical adsorption rather than chemical interaction (Fig. 5).…”
Section: Computational Methodologymentioning
confidence: 93%